(untitled) (Journal of Open Law, Technology & Society, 2010)
Andrew Katz reviews the Third Edition of Law and the Internet (ed. Edwards and Waelde, 2009), with particular emphasis on chapters 10, 11 and 12, covering the legal protection of computer software, free and open source software, and open access, respectively.